Improving coverage of indoor millimetre wave systems using spherical reflectors - Priya A. Qualtrough‐Mittal; Michael J. Neve; Andrew C. M. Austin (IET Microwaves, Antennas & Propagation)
Abstract The increased demand for user device connectivity has led to spectral congestion which is driving exploration of higher frequency spectrum, such as millimetre wave frequencies. As millimetre wave propagation is predominantly line‐of‐sight, shadowing becomes prevalent in indoor environments due to obstructions from clutter. Accordingly, there is a need to find solutions which can provide additional coverage. In this work, octant‐shaped spherical reflectors are deployed in small office environments with varying degrees of clutter to provide additional ray paths to improve millimetre wave coverage into shadow regions. Cost weightings have been allocated to prioritise regions of high importance and are used to compare reflector deployment strategies. Appropriate positioning of reflectors in the environment is shown to improve coverage into shadow regions in all three environments considered, with placement in the top corners of a room found to be a valid solution. In densely cluttered environments, more than one reflector may be required to provide sufficient coverage. Reducing the reflector radius by 0.1 m has been shown to increase reflected power by up to 6 dB in some cases.